Trafficking in women and children in India - Nair, P. M., 1953- (Orient Longman, 2005)
This book presents the research findings of Action Research on Trafficking in Women and Children in India (ARTWAC) that involved the United Nations Development Fund for Women, the National Human Rights Commission and the Institute of Social Sciences. Through a human rights perspective, the first section of this book analyses the data generated by ARTWAC and gives detailed recommendations for better judicial interventions, law enforcement and community participation in anti-trafficking strategies. The second section contains a rich collection of case studies, giving an on-ground picture of how exploiters have little or no respect for the rights of trafficking victims.